Is there a role for perfusion imaging in assessing treatment response following ablative therapy of small renal masses—A systematic review. (2018) - Withey, S.J.; Gariani, J.; Reddy, K.; Prezzi, D.; Kelly-Morland, C.; Ilyas, S.; Adam, A.; Goh, V.
Abstract: Aims: Ablation therapies are an innovative nephron-sparing alternative to radical nephrectomy for early stage renal cancers, although determination of treatment success is challenging. We aimed to undertake a systematic review of the literature to determine whether assessment of tumour perfusion may improve response assessment or alter clinical management when compared to standard imaging. Material and Methods: Two radiologists performed independent primary literature searches for perfusion imaging in response assessment following ablative therapies (radiofrequency ablation and cryotherapy) focused on renal tumours. Results: 5 of 795 articles were eligible, totaling 110 patients. The study designs were heterogeneous with different imaging techniques, perfusion calculations, reference standard and follow-up periods. All studies found lower perfusion following treatment, with a return of 'high grade' perfusion in the 7/110 patients with residual or recurrent tumour. One study found perfusion curves were different between successfully ablated regions and residual tumour. Conclusions: Studies were limited by small sample size and heterogeneous methodology. No studies have investigated the impact of perfusion imaging on management. This review highlights the current lack of evidence for perfusion imaging in response assessment following renal ablation, however it suggests that there may be a future role. Further prospective research is required to address this.